Smoking under the tsars : a history of tobacco in imperial Russia - Starks, Tricia, 1969- (Cornell University Press, 2018)
"Using unusual sources and approaching tobacco from the perspective of users, producers, and objectors, this monograph provides a view of the early transfer by the Russian market to smoking and presents the addictive, nicotine-soaked Russian cigarette - the papirosa - and the sensory, medical, social, cultural, and gendered consequences of this unique style of tobacco use"-- Provided by publisher.
Keywords: Smoking -- Russia -- History -- 19th century.; Russians -- Tobacco use -- History.; Tobacco -- Social aspects -- Russia -- History.; Russia -- Social conditions -- 1801-1917.; Tabagisme -- Russie -- Histoire -- 19e siècle.; Russes -- Tabagisme -- Histoire.; Tabac -- Aspect social -- Russie -- Histoire.; Russie -- Conditions sociales -- 1801-1917.; SOCIAL SCIENCE -- Agriculture & Food.; HISTORY -- Europe -- Russia & the Former Soviet Union.; Smoking; Social conditions; Tobacco -- Social aspects; Russia; 1800-1917; History